What we should know about whitening toothpastes. - Palomino-Granados, Roberto Carlos (2022)
The color of teeth can be altered by pigmenting or chromogenic substances, by retention in the dental biofilm, bacterial plaque or by chemical alteration of the tooth surface. Among the products available to remove these pigmentations, in order to maintain the color of natural teeth, there are whitening toothpastes, which have the characteristic of being freely available and can be purchased without a prescription. These toothpastes use mechanical, chemical or physical mechanisms and do not cause greater abrasion of the enamel when compared to conventional toothpastes. The aim of this review article was to evaluate the evidence on the efficacy of whitening toothpastes on tooth color and to verify the potential risks of their frequent use.